Problematika Penetapan Ṭayyib dalam Kosmetik Halal: Telaah Fiqh dan Epistemologi Hukum Islam Kontemporer - Afifah Nabil Hasna Aisy (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2026)
The rapid growth of the halal cosmetics industry requires an assessment framework that goes beyond ingredient legality and incorporates the principle of ṭayyib, which emphasizes cleanliness, safety, and product benefit. The increasing complexity of modern cosmetic formulations, many of which contain synthetic compounds with potential health risks, reveals a gap between existing halal certification mechanisms and the normative demands of ṭayyib within Islamic jurisprudence. This study aims to clarify the conceptual construction of ṭayyib in fiqh, identify the epistemological challenges in evaluating contemporary cosmetic products, and propose an integrative model grounded in maqāṣid al-sharī‘ah and established legal maxims. This research employs a qualitative descriptive design through document analysis of fiqh literature, maqāṣid theory, legal maxims, and scientific studies related to cosmetic safety. The findings demonstrate that ṭayyib functions as a legal category requiring protection from harm, thereby necessitating an integration of halal verification with empirical assessment of ingredient risks. The complexity of modern cosmetics is not yet fully addressed by current halal certification standards. This study concludes that national halal regulations should incorporate safety parameters to ensure that halal cosmetics genuinely reflect ṭayyib values and provide optimal protection for Muslim consumers.